Voltage analysis

Discussion in 'Homework Help' started by Teszla, Jun 23, 2013.

  1. Teszla

    Thread Starter Member

    Jun 7, 2013

    I have some questions about the voltage analysis (see image above).

    * In this case, would the expression for Vp be Vp = V1-V2? More exact: is it the polarity of Vp that decides how the expression of Vp looks?
    * Is the expression of Vp independent from the reference node, as long as the supernode around Vp is not including the reference node?
  2. Jony130

    AAC Fanatic!

    Feb 17, 2009
    Your expression looks good for me. If you reverse Vp voltage polarity then Vp = V2 - V1 or -Vp = V1 - V2
    But for this circuit we already know all the voltage.
    V1 = Vs and V2 = Vs - Vp so we don't need Vp = V1 - V2